A Review of Worldwide Patents: Innovations in Peak Flow Meters for Asthma. Issue 3 (May 2016) - Klingman, Karen J.; Castner, Jessica; Titus, Albert H.
Abstract : Background: Contemporary healthcare nurses increasingly rely on innovative technology for assessment, treatment, and patient self-management. Funding opportunities as well are increasingly steering toward technology development and innovation. Health researchers, including nursing scientists, who are engaged in medical device innovation need to assess the state of the art of current technology. This requires an intellectual property analysis, or patent search, which is not covered by the types of literature reviews customarily used in health science research. Purpose: The purposes of this article are to illustrate a methodical review of worldwide patents and to show how those results can be used to identify possible products available for use. Approach: An application of peak flow meters for use by patients with asthma is used to illustrate the process. The Derwent Innovations Index interface with keyword searching is illustrated, as is the use of Google Patents. From the 14 patent document results, six possible technologies were identified. The patent search revealed innovations in asthma peak flow meters for use in future research and identified future directions for device development. Discussion: These results support the claim that patent literature must be included in reviews that seek to identify technology state-of-the-art healthcare applications and that advances in the nursing research paradigm should include patents as background and scholarly products.